A facile preparation of immobilized naringinase on polyethyleneimine-modified Fe3O4 magnetic nanomaterials with high activity. Issue 24 (19th April 2021) - Yu, Chan; Li, Qian; Tian, Jing; Zhan, Honglei; Zheng, Xinyu; Wang, Shujing; Sun, Xitong; Sun, Xiyan
Abstract : Polyethyleneimine-modified Fe3 O4 nanoparticles (Fe3 O4 -PEI) were synthesized by the one-step co-precipitation method, and the resulting material was used to immobilize naringinase from the fermentation broth of Aspergillus niger FFCC uv-11. Abstract : Polyethyleneimine-modified Fe3 O4 nanoparticles (Fe3 O4 -PEI) were synthesized by the one-step co-precipitation method, and the resulting material was used to immobilize naringinase from the fermentation broth of Aspergillus niger FFCC uv-11. The immobilized naringinase activity could reach up to 690.74 U per g-support at the conditions of initial naringinase activity of 406.25 U mL −1, immobilization time of 4 h, glutaraldehyde concentration of 40% (w/v), immobilization temperature of 35 °C, and pH value of 5.5, with naringinase-carrying rate and naringinase activity recovery of 92.93% and 20.89%, respectively. In addition, the immobilized naringinase exhibited good pH and temperature stability in a pH range of 3.5–6.0 and temperature range of 40–70 °C, and the optimal reaction pH and reaction temperature were optimized as 5.5 and 60 °C, respectively. Besides, the immobilized naringinase could maintain 60.58% of the original activity after 10 reuse cycles, indicating that the immobilized naringinase had good reusability. Furthermore, the immobilized naringinase also performed excellent storage stability, 87.52% of enzyme activity still remained as stored at 4 °C for one month. In conclusion, the Fe3 O4 -PEI could be considered as a promising support for naringinase immobilization, with the advantages of high enzyme activity loading, good reusability, storage stability and rapid recovery.